Regularization and singular perturbation techniques for non-smooth systems - Teixeira, Marco Antonio; da Silva, Paulo Ricardo [UNESP] (Elsevier B.V., 2012)
This paper is concerned with some aspects of the qualitative-geometric theory of non-smooth systems. We present a survey of the state of the art on the connection between the regularization process of nonsmooth vector fields and the singular perturbation problems. As a matter of fact, the main results in our setting fill a gap between these areas. Exploiting such results, applications to constrained differential equations are discussed. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Regularization; Vector field; Constrained system; Singular perturbation; Non-smooth vector field; Sliding vector field